Numerical Simulation of Heat and Mass Transfer during Absorption of Hydrogen in Metal Hydride Tank. Issue 1 (14th September 2015) - Rabienataj Darzi, A.A; Hassanzadeh Afrouzi, H.; Alizadeh, Ebrahim; Shokri, Vahid; Farhadi, Mousa
Abstract : The present study is concerned with cooling a metal hydride tank during the charging process by using a water jacket and fins. Results indicate that the effect of the water jacket becomes more significant over time. Variation of the Reynolds number has no influence on the charging time in the turbulent regime while changing the flow regime from laminar to turbulent improves the results slightly. Furthermore, adding fins on the cooling jacket enhances the heat transfer significantly through better removal of the heat from the central region of the metal bed. Hence, the charging time was significantly reduced.